Analisis Kecenderungan Pemakaian Portal ‘Distribution Store’ oleh Kawula Muda - Tjahjani, Indra (Journal the Winners: Economics, Business, Management, and Information System Journal, 2006)
The development of industry trend fashion in Indonesia increased rapidly. The monetary crises in 1998 pushed the fashion industry more. The youngster tried to produce their own Identity group by themselves. It was started by Skater Group from Bandung 347, from Jakarta Locker and, followed by Cynical MD. The fashion that they introduced to the young people became trendsetter. Their business was known as Indie Label (shorten for Independent Label) and their shop is called Distro (shorten for Distribution Store), a small shop that sold community merchandises. Amazingly the buyers or costumer came from all over big cities in Indonesia.